Pengaruh perceived sustainability terhadap destination trust dan word of mouth intention pada wisatawan Pantai Lon Malang - Nurisa Nurisa; Deykha Aguilika (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study aims to determine the effect of perceived sustainability on destination trust and word of mouth intention among tourists at Lon Beach, Malang, Sampang Regency. The research method used is a quantitative approach. The data used are primary and secondary data. The sample in this study amounted to 130 respondents with a non-probability sampling technique using a purposive sampling method. The characteristics of the respondents used are tourists who have visited Lon Beach, Malang in the past year and are at least 17 years old. Data collection was carried out through questionnaires and processed using the SmartPLS version 4 application. The results of the study indicate that perceived sustainability has a significant effect on destination trust and word of mouth intention. In addition, the results of the path coefficient analysis indicate that destination trust plays a significant mediating variable in the relationship between perceived sustainability and word of mouth intention.